Identidades Trigonométricas

 

$csc(\theta)=\frac{1}{sen(\theta)} $

$sen(-\theta)=-sen(\theta) $
$tan(\theta)= \frac{sen(\theta)}{cos(\theta)} $  $cos(-\theta)=cos(\theta) $
$1+ tan^2(\theta) = sec^2(\theta) $ $tan(-\theta)=-tan(\theta) $  





 

$sen\left({\pi\over 2}-\theta \right)=cos(\theta) $ $sec(\theta)=\frac{1}{cos(\theta)} $
$cos\left({\pi\over 2}-\theta \right)=sen(\theta) $ $cot(\theta)=\frac{cos(\theta)}{tan(\theta)} $
$tan\left({\pi\over 2}-\theta \right)=cot(\theta) $ $1+cot^2(\theta) = csc^2(\theta) $

 

Suma y Resta de ángulos

 

 $sen(\theta+\omega)=sen(\theta)cos(\omega)+cos(\theta)sen(\omega) $ $sen(\theta-\omega)=sen(\theta)cos(\omega)-cos(\theta)sen(\omega) $
$cos(\theta+\omega)=cos(\theta)cos(\omega)-sen(\theta)sen(\omega) $ $cos(\theta-\omega)=cos(\theta)cos(\omega)+sen(\theta)sen(\omega) $
$tan(\theta+\omega)=\frac{tan(\theta)+tan(\omega)}{1-tan(\theta)tan(\omega)} $ $tan(\theta-\omega)=\frac{tan(\theta)-tan(\omega)}{1+tan(\theta)tan(\omega)} $

 

Productos

 

$sin^2(\theta)=\frac{1}{2}(1-cos(2\theta)) $ $cos^2(\theta)=\frac{1}{2}(1+cos(2\theta)) $
$sen(\theta)cos(\theta)=\frac{1}{2}(sen(2\theta)) $ $sen(\theta)sen(\omega)=\frac{1}{2}(cos(\theta-\omega)-cos(\theta+\omega)) $
$sen(\theta)cos(\omega)=\frac{1}{2}(sen(\theta-\omega)+sen(\theta+\omega)) $ $cos(\theta)cos(\omega)=\frac{1}{2}(cos(\theta-\omega)+cos(\theta+\omega)) $

 

Otras fórmulas

 

$sen(2\theta)=2sen(\theta)cos(\theta)$ $cos(2\theta)=cos^2(\theta)-sen^2(\theta)$
$cos(2\theta)=2cos^2(\theta)-1$ $tan(2\theta)=\frac{2tan(\theta)}{1-tan^2(\theta)}$

Additional information